Pengembangan Media Iqra Semar Untuk Peningkatkan Keterampilan Membaca Huruf Jawa Siswa SD Kelas IV - Istiningsih, Galih; Martinah, Martinah (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
The purpose of this study was to determine (1) the characteristics, (2) the validity of (3) practicality, (4) the effectiveness iqra SEMAR media. This research is a Research and Development, the research design developed by Borg and Gall ie step preliminary study, development, and testing results. Assessed the validity of the instrument and its learning mediasupporting the learning medias such as: lesson plans, Teaching Material, LKS, THB, and Iqra Books Java. Practicality assessed from teacher observation sheet to manage learning, student responses and teacher responses. Assessed the effectiveness of the activities of students, THB and reading skills. Analysis using descriptive, descriptive percentages and THB using n-gain techniques were then tested one sample test and the test sample pair. Iqra SEMAR media on reading skills in elementary students letters Java class IV characteristics from the syntagmatic, social systems, reaction principle, the principle and the impact of instructional support or accompaniment. Research results that cooperative learning mediato learning reading skills Herroiq Java letter declared valid. expert validation score of 89.9 for the learning media (very valid); learning device at 66 (very valid); RPP of 221 (very valid); teaching materials for 143.6 (valid); LKS equal to 151 (very valid); THB at 169.8 (very valid); book iqra at 156.6 (very valid). Iqra SEMAR media to learning the skills to read Java skill. Score observations ability of teachers to manage learning has a score of 3.43 (very good); responses of the students had an average score of 3.23 (very good); responses teacher of the learning activities obtained an average score was 3.41 or teacher response to the criteria (excellent). Results of analysis of student activity 81.25; median student learning outcomes by 87, with a value of t is greater than t table (9.493> 2.04523), reflecting the significant differences of learning to iqra SEMAR media.